X-ray micro-computed tomography (μCT): an emerging opportunity in parasite imaging. Issue 7 (28th November 2017) - O'Sullivan, James D. B.; Behnsen, Julia; Starborg, Tobias; MacDonald, Andrew S.; Phythian-Adams, Alexander T.; Else, Kathryn J.; Cruickshank, Sheena M.; Withers, Philip J.
Abstract: X-ray micro-computed tomography ( μ CT) is a technique which can obtain three-dimensional images of a sample, including its internal structure, without the need for destructive sectioning. Here, we review the capability of the technique and examine its potential to provide novel insights into the lifestyles of parasites embedded within host tissue. The current capabilities and limitations of the technology in producing contrast in soft tissues are discussed, as well as the potential solutions for parasitologists looking to apply this technique. We present example images of the mouse whipworm Trichuris muris and discuss the application of μ CT to provide unique insights into parasite behaviour and pathology, which are inaccessible to other imaging modalities.